The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1098/rstb.2021.0510
|View full text |Cite
|
Sign up to set email alerts
|

Assessing pollen nutrient content: a unifying approach for the study of bee nutritional ecology

Abstract: Poor nutrition and landscape changes are regularly cited as key factors causing the decline of wild and managed bee populations. However, what constitutes ‘poor nutrition’ for bees currently is inadequately defined. Bees collect and eat pollen: it is their only solid food source and it provides a broad suite of required macro- and micronutrients. Bees are also generalist foragers and thus the different pollen types they collect and eat can be highly nutritionally variable. Therefore, characterizing the multidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 117 publications
0
20
0
Order By: Relevance
“…The physiological mechanism of such a tradeoff and its ecological consequences constitute an interesting topic for future studies. Importantly, this study shows that, as suggested earlier Lau et al, 2022;Parreño et al, 2022), a holistic approach to the chemical composition of pollen, complementary to the most common currently used examination of the concentration and proportion of proteins and lipids, is necessary to develop our understanding of the nutritional ecology of bees and consequently their health.…”
Section: Discussionmentioning
confidence: 75%
“…The physiological mechanism of such a tradeoff and its ecological consequences constitute an interesting topic for future studies. Importantly, this study shows that, as suggested earlier Lau et al, 2022;Parreño et al, 2022), a holistic approach to the chemical composition of pollen, complementary to the most common currently used examination of the concentration and proportion of proteins and lipids, is necessary to develop our understanding of the nutritional ecology of bees and consequently their health.…”
Section: Discussionmentioning
confidence: 75%
“…The analysis of Brassica and Rosa pollens [ 54 ] included major elements: this area of pollinator nutrition is receiving increased attention and may be important for the health of honeybee colonies [ 56 ]. De Sousa et al [ 57 ] tested the dose-related responses of young worker honeybees in cages to mineral-laced sucrose solutions.…”
Section: Nutrients In Nectar and Pollen And Their Importance For Poll...mentioning
confidence: 99%
“…Differences in methods make it difficult to compare studies. In this issue, Lau et al [54] review the common methods used to analyse pollen protein and lipids-the macronutrients most often linked to bee health. Using Brassica and Rosa pollens, they compared a subset of these methods while also carrying out a more complete analysis.…”
Section: Nutrients In Nectar and Pollen And Their Importance For Poll...mentioning
confidence: 99%
“…The nutritional needs of honey bees vary seasonally as the colony lifecycle follows a progression of brood development, colony growth, and overwintering (DeGrandi-Hoffman et al 2021). Any deviation from optimal nutritional levels poses significant risks to the physiological attributes in bees (Stabler et al 2015) and bees exhibit distinct strategies to balance uptake of nutrients (Paoli et al 2014, Reade and Naug 2016, Lau et al 2022).…”
Section: Introductionmentioning
confidence: 99%